The Philosophy of Divinity: From Platonism to Orthodoxy – A Study in the Thought of Theodoret of Cyrrhus - Saiid, Rony Emil (Arab Journal for Sciences and Research Publishing, 2025)
This study addresses the question of divinity by examining the thought of Theodoret of Cyrrhus, one of the most prominent Fathers of the Eastern Church in the fifth century AD. The study is based on his work Therapeutics of Hellenic Maladies, where we analyzed his arguments against Greek philosophers, particularly the Platonists. We deconstructed Greek philosophical concepts through critique and analysis and compared them with Orthodox Christian principles. The study aims to introduce readers to Orthodox Christian thought in its philosophical and logical aspects, challenge the stereotypical view that separates faith from reason, and highlight the significance of Greek philosophy and the originality of Theodoret of Cyrrhus. Furthermore, The study concluded that the Platonic conception of divinity was significantly influenced by Jewish thought based on divine revelation. However, the Platonic God remained an abstract idea, confined to the realm of the first cause, without arriving at the notion of a personal God advocated by Theodoret. Additionally, the research concluded that the "Trinity" is not a concept invented by Christianity but rather the same monotheistic belief found in the Old Testament and some Platonic writings influenced by it. This research contributes significantly to the Arabic academic library and opens new horizons for further studies on the relatively unexplored field of Eastern Christian philosophy (Orthodoxy) in academic circles.